Revealing Key Determinants of Clonal Variation in Transgene Expression in Recombinant CHO Cells Using Targeted Genome Editing - Lee, Jae Seong; Park, Jin Hyoung; Ha, Tae Kwang; Samoudi, Mojtaba; Lewis, Nathan E.; Palsson, Bernhard O.; Kildegaard, Helene Faustrup; Lee, Gyun Min (ACS Synthetic Biology, 2018)
Generation of recombinant Chinese hamster ovary (rCHO) cell lines is critical for the production of therapeutic proteins. However, the high degree of phenotypic heterogeneity among generated clones, referred to as clonal variation, makes the rCHO cell line development process inefficient and unpredictable. Here, we investigated the major genomic causes of clonal variation. We found the following: (1) consistent with previous studies, a strong variation in rCHO clones in response to hypothermia (33 vs 37 °C) after random transgene integration; (2) altered DNA sequence of randomly integrated cassettes, which occurred during the integration process, affecting the transgene expression level in response to hypothermia; (3) contrary to random integration, targeted integration of the same expression cassette, without any DNA alteration, into three identified integration sites showed the similar response of transgene expression in response to hypothermia, irrespective of integration site; (4) switching the promoter from CMV to EF1α eliminated the hypothermia response; and (5) deleting the enhancer part of the CMV promoter altered the hypothermia response. Thus, we have revealed the effects of integration methods and cassette design on transgene expression levels, implying that rCHO cell line generation can be standardized through detailed genomic understanding. Further elucidation of such understanding is likely to have a broad impact on diverse fields that use transgene integration, from gene therapy to generation of production cell lines.
Keywords: Animals; CHO Cells; Cricetinae; Cricetulus; Cytomegalovirus; Gene Editing; Gene Expression; Green Fluorescent Proteins; Peptide Elongation Factor 1; Promoter Regions, Genetic; Regulatory Sequences, Nucleic Acid; Temperature; Transgenes; Chinese hamster ovary cells; clonal variation; integration site; targeted integration; vector configuration